DETERMINANT FACTORS OF MILLENNIAL PARENTS IN SUPPORTING EARLY CHILDHOOD DEVELOPMENT - Tria Wahyuningrum (International Journal of Nursing and Midwifery Science (IJNMS), 2026)
Early childhood development encompasses aspects of physical, cognitive, social-emotional, social context, moral, language, self-identity, and gender development. The age range of 0–6 years is a crucial period in shaping a child's future character, including attitudes, behavior, and personality. The preschool age (under five) is also considered a golden period for parents to optimally develop their child's potential (Andayani, 2021). This study aimed to analyze the parental determinants, including the educational level, employment status, and economic status of Millennial parents, on early childhood development. A quantitative cross-sectional approach was used, involving 177 children aged 42–72 months and their parents at PAUD Al Izzah Puri Mojokerto. Child development was measured using the Pre-Screening Development Questionnaire (KPSP) and analyzed using the Chi-Square test with a significance level of 0.05. The results showed no significant relationship between educational level (p=0.534) and economic status (p=0.641) and child development. However, a significant relationship was found between maternal employment status and child development (p=0.037). These findings emphasize that parenting factors and the quality of interaction are more determinative of child development than certain demographic characteristics.